2015
DOI: 10.1074/mcp.m115.053926
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Insights into Classical and Alternative Activation States of Microglia as Revealed by Stable Isotope Labeling by Amino Acids in Cell Culture (SILAC)-based Proteomics*

Abstract: Microglia, the resident immune cells of the brain, have been shown to display a complex spectrum of roles that span from neurotrophic to neurotoxic depending on their activation status. Microglia can be classified into four stages of activation, M1, which most closely matches the classical (pro-inflammatory) activation stage, and the alternative activation stages M2a, M2b, and M2c. The alternative activation stages have not yet been comprehensively analyzed through unbiased, global-scale protein expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 44 publications
(64 reference statements)
3
50
0
Order By: Relevance
“…Alveolar MØs are the main source of cathepsins in bleomycin-induced fibrotic lung tissue [43]. Additional genes associated with development and maintenance of alternative MØ activation include TGFBI [44], NEU1 [45], PRCP [46], and DAB2 [47]. Genes that are specifically associated with alternative activation of lung MØs include PLP2 [48] and IFITM1 [49] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar MØs are the main source of cathepsins in bleomycin-induced fibrotic lung tissue [43]. Additional genes associated with development and maintenance of alternative MØ activation include TGFBI [44], NEU1 [45], PRCP [46], and DAB2 [47]. Genes that are specifically associated with alternative activation of lung MØs include PLP2 [48] and IFITM1 [49] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All of these results in vivo and in vitro studies indicated that α-LA exerts neuroprotective effects by inducing the polarization of microglia to the M2 phenotype. Previous studies indicated that microglia show a transient M2 phenotype in the ischemic penumbra and express high levels of anti-inflammatory factors to improve neuron survival and reduce cerebral infarct volume within 24 h after ischemic stroke [28,29]. Then, activated microglia shift to the M1 phenotype and worsen tissue destruction and neurological dysfunction.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In the context of TBI, IL-10 is demonstrably higher intrathecally and has been shown to activate the anti-inlammatory subtype of microglia (phenotypically referred to as M2 microglia) involved in matrix formation and the remodeling of tissue [169][170][171]. In a study examining IL-10 in TBI, Knoblach et al administered intravenous IL-10 at 30 min prior to and 1 h after lateral luid percussion TBI in rats.…”
Section: Anti-inlammatory Il-10 In Tbimentioning
confidence: 99%
“…IL-4 and IL-13 can activate the M2a polarization state of microglia, an anti-inlammatory microglia subtype and may be an avenue for potential therapy post-TBI [169,171]. Clinically, in patients undergoing surgery post-severe TBI, IL-4 expression levels were increased in the irst 24 h post-injury in brain tissue samples, while lower IL-4 levels were present in patients undergoing surgery on days 3-5 post-injury; in the late group, IL-4 levels were also signiicantly lower than IL-1β and IFN-γ levels [145].…”
Section: Anti-inlammatory Il-4 In Tbimentioning
confidence: 99%